2022
DOI: 10.1111/1744-7917.12999
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of pheromone biosynthesis and mating behavior by RNA interference of pheromone gland‐specific fatty acyl reductase in Maruca vitrata

Abstract: In moths, various enzymes, such as fatty acid synthases, fatty acyl desaturases, and fatty acyl reductases (FARs), are involved in pheromone biosynthesis. In particular, pheromone gland‐specific FAR (pgFAR) plays an important role in converting the functional group from carboxylic to alcohol during pheromone biosynthesis. A novel pgFAR of Maruca vitrata, Mvi‐pgFAR, was identified through transcriptome sequencing of its pheromone gland. To investigate the involvement of Mvi‐pgFAR in pheromone biosynthesis, Mvi‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In this study, prior to RNAi treatment, we measured the diurnal expression of MviPBANR-C in response to MviPBAN in the pheromone glands of M. vitrata. The expression level of MviPBANR-C was the highest at 2 h before the scotophase (5 p.m.) (Figure 5), which coincides with MvipgFAR expression [26]. RNAi suppression of MviPBANR-C was performed 2 h before the scotophase (5 p.m.), and this suppression reduced sex pheromone production as well as mating behavior (Figure 5).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, prior to RNAi treatment, we measured the diurnal expression of MviPBANR-C in response to MviPBAN in the pheromone glands of M. vitrata. The expression level of MviPBANR-C was the highest at 2 h before the scotophase (5 p.m.) (Figure 5), which coincides with MvipgFAR expression [26]. RNAi suppression of MviPBANR-C was performed 2 h before the scotophase (5 p.m.), and this suppression reduced sex pheromone production as well as mating behavior (Figure 5).…”
Section: Discussionmentioning
confidence: 64%
“…In addition, PBAN, which induces sex pheromone biosynthesis, was found in the heads of female adults of M. vitrata [25]. Functional analysis using RNA interference (RNAi) revealed that pheromone gland-specific fatty acyl reductase (pgFAR) was also involved in the sex pheromone biosynthesis of M. vitrata [26]. However, signal transduction studies on PBANR in M. vitrata remain insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of Sf‐PBANr may lead to decrease pheromone production, which results in unsuccessful mating behaviour as mismatching with female and male during mating period in adult stage. Some studies have reported that suppression of genes, which are related with pheromone production, reduced mating rate in Maruca vitrata (Cha & Lee, 2022) and in P. xylostella (Lee et al, 2011). Therefore, silencing of PBANr gene by RNAi suggest that the gene is closely related with sex pheromone biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…7.1.0.). Phylogenetic trees for the alignment were constructed using the Maximum likelihood method and the Jones–Taylor–Thornton model (Cha & Lee, 2022; Lee et al, 2022).…”
Section: Methodsmentioning
confidence: 99%